STRATEGI PEMENUHAN KEBUTUHAN MASYARAKAT MASA REPLANTING UNTUK MENINGKATKAN PEREKONOMIAN DESA PINANG GADING KABUPATEN TANJUNG JABUNG BARAT - Agung Nur Arobi; Bambang Kurniawan; G.W.I. Awal Habibah (Fakultas EKonomi dan Bisnis Islam UIN Sulthan Thaha SAifuddin Jambi, 2026)
This study aims to describe the economic condition of oil palm farmers during the replanting period and analyze the strategies adopted to meet household needs from an Islamic economic perspective. This research employed a descriptive qualitative approach with data collected through interviews, observations, and documentation. The data were analyzed thematically to capture the dynamics of farmers’ livelihoods and the Islamic values embedded in their strategies. The results indicate that farmers experienced a significant income decline. Before replanting, income ranged from IDR 3,700,000–6,500,000 every two weeks, while during replanting it dropped to IDR 0–2,500,000 per month, with households averaging 3–6 members. To cope, farmers adopted various strategies such as reducing expenditures, cultivating secondary crops, opening small shops, working as daily laborers, trading goods, raising livestock, renting vehicles, and utilizing rental houses. From the Islamic perspective, these efforts reflect values such as working hard for halal income, maintaining ethics, practicing qana’ah (contentment), fostering social solidarity, and prioritizing good character.